Hubungan Karakteristik Sosial Ekonomi Dengan Partisipasi Masyarakat Dalam Pelaksanaan Agroforestri Di Desa Bungku Kabupaten Batanghari - Leilea Azizathul Mukhtiya; Marwoto; Hamzah (Jurnal Pembangunan Berkelanjutan, 2023)
This study aims to analyze the relationship between socio-economic characteristics and community participation. Analysis of the relationship between socio-economic characteristics and participation was tested by cross-tabulation test crossta-correlations and analysis of perceptions and participation and determining the categories using 3 (three) Likert scale points and score interval equations. The results show the value of Approx. Sig is 0.046 then the value is Approx. Sig Spearman Correlation < α (0.05) then H0 is rejected thus there is a relationship between socio-economic characteristics (age, education, arable area, distance to agroforestry, income per month, number of family dependents, farming experience, cosmopolitan) with perceptions and participation of KTH members in agroforestry implementation activities.